EVALUATION OF PAROTIDECTOMY OUTCOMES IN THE TREATMENT OF PLEOMORPHIC ADENOMA OF THE PAROTID GLAND AT MILITARY HOSPITAL 103 (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the surgical outcomes in patients with pleomorphic adenoma of the parotid gland at Military hospital 103.Materials and Methods: This prospective study involved 22 patients diagnosed with pleomorphic adenoma of the parotid gland, who underwent surgery at the Department of Maxillofacial and Reconstructive Surgery, Military Hospital 103, from January 2023 to December 2024. Postoperative complications were monitored and evaluated at 1 week, 1 month, 3 months, and 6 months after surgery.Results: The majority of patients (63.6%) underwent superficial parotidectomy. The rate of facial paralysis decreased over time: 81.8% at 1 week, 50.0% at 1 month, 27.3% at 3 months, and 0% at 6 months. By 6 months postoperatively, all patients had recovered normal facial motor function (House-Brackmann grade I). Complications included hematoma (4.5%) and salivary fistula (4.5%). There were no cases of surgical site infection, Frey syndrome, or tumor recurrence during follow-up.Conclusion: Parotidectomy with facial nerve preservation is an effective and relatively safe surgical approach for the treatment of pleomorphic adenoma. Although early postoperative facial paralysis was relatively common, most patients achieved complete recovery within 6 months.
Keywords: Pleomorphic adenoma of the parotid gland; Parotid gland surgery; Facial nerve preservation; Surgical outcomes.